2006
DOI: 10.1016/j.addbeh.2005.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine dependence, PTSD symptoms, and depression proneness among male and female smokers

Abstract: Several studies have linked posttraumatic stress disorder with heavy smoking. It is not known to what extent this association is specific, as opposed to being a function of a joint association of PTSD and heavy smoking with a third variable such as depression proneness. In a cross-sectional study of 157 current regular smokers, severity of nicotine dependence (but not cigarettes smoked per day) was positively correlated with total PTSD symptoms, hyperarousal symptoms, and avoidance symptoms. These correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 24 publications
0
53
3
Order By: Relevance
“…Smith et al, 1999 Descriptive Oklahoma city residents reported higher rates of (1) trauma exposure, (2) PTSD symptoms, (3) smoking, (4) increased smoking, and (5) smoking initiation compared to Indianapolis residents. Thorndike et al, 2006 Regression Among men, nicotine dependence levels were positively associated with total PTSD symptoms as well as the hyperarousal, avoidance, and reexperiencing symptoms, even after statistically controlling for depression proneness and past history of major depressive episodes among men. These relations were not apparent among women.…”
Section: Author(s)/ Year Analytic Approach Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Smith et al, 1999 Descriptive Oklahoma city residents reported higher rates of (1) trauma exposure, (2) PTSD symptoms, (3) smoking, (4) increased smoking, and (5) smoking initiation compared to Indianapolis residents. Thorndike et al, 2006 Regression Among men, nicotine dependence levels were positively associated with total PTSD symptoms as well as the hyperarousal, avoidance, and reexperiencing symptoms, even after statistically controlling for depression proneness and past history of major depressive episodes among men. These relations were not apparent among women.…”
Section: Author(s)/ Year Analytic Approach Resultsmentioning
confidence: 94%
“…Thorndike, Wernicke, Pearlman, and Haaga (2006) examined the relations between nicotine dependence levels, PTSD symptoms, and gender among daily smokers. Participants were excluded on the basis of current depressive episodes and moderate levels of depressive symptoms (Beck Depression Inventory scores ≥ 16; Beck, Rush, Shaw, & Emery, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, human studies also showed that PTSD symptoms are altered by nicotine dependence. For example, several studies have shown that severity of nicotine dependence was correlated with total PTSD symptoms (Thorndike et al 2006). There is also evidence showing that PTSD patients show altered contextual information processing during extinction (Rougemont-Bücking et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking rates among PTSD patients (45.3%) are significantly higher than the nonclinical population (22.5%, Ziedonis et al 2008). In addition, a significant positive correlation exists between smoking and PTSD symptoms and the severity of PTSD symptoms is predicted by daily number of cigarettes smoked (Thorndike et al 2006;Greenberg et al 2012). Beyond PTSD, smoking rates increase when healthy individuals encounter stressful/anxiogenic situations (Pomerleau and Pomerleau 1987).…”
mentioning
confidence: 97%
“…Depressive symptoms also demonstrate a strong relationship with smoking behavior and nicotine dependence [13,14]. However, the potential confound of depression has been accounted for in a limited number of studies on trauma exposure and smoking [15].…”
Section: Introductionmentioning
confidence: 99%